2011
DOI: 10.1111/j.1365-2095.2011.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Different utilization of plant sources by the omnivores jundiá catfish (Rhamdia quelen) and Nile tilapia (Oreochromis niloticus)

Abstract: Plant sources are receiving special attention as feedstuffs in aquafeeds because of fish meal and oil shortage. However, studies about the effects of dietary fibre in fish are scarce. The inclusion of plant ingredients containing different levels of dietary fibre -broken rice (BR), ground corn (GC), wheat bran (WB), citrus pulp (CP) and soybean hulls (SH) were evaluated for the omnivores jundia´catfish and Nile tilapia. Tilapia is a typical omnivore with long intestines, whereas jundia´has short intestines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
0
35
1
5
Order By: Relevance
“…Zhou et al () found a lower ADCDM (84.6%), but similar ADCGE (94.2%) and ADCCP (94.4%) for corn gluten meal fed to cobia, Rachycentron canadum . It is more difficult for carnivorous fish and omnivores with carnivorous tendencies to digest plant‐derived nutrients than it is for herbivorous fish or omnivores with herbivorous tendencies (NRC ; Rodrigues et al ). Levels of amylolytic and proteolytic activity in the digestive tract vary widely among fish with different feeding habits (Hidalgo et al ), which reflects differential ability to digest energy and nutrients from plant materials (Bakke et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al () found a lower ADCDM (84.6%), but similar ADCGE (94.2%) and ADCCP (94.4%) for corn gluten meal fed to cobia, Rachycentron canadum . It is more difficult for carnivorous fish and omnivores with carnivorous tendencies to digest plant‐derived nutrients than it is for herbivorous fish or omnivores with herbivorous tendencies (NRC ; Rodrigues et al ). Levels of amylolytic and proteolytic activity in the digestive tract vary widely among fish with different feeding habits (Hidalgo et al ), which reflects differential ability to digest energy and nutrients from plant materials (Bakke et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Nile tilapia is a typical omnivore, with long intestines and physiological adaptations to tolerate higher inclusion of dietary plant sources (RODRIGUES et al, 2012;GOMINHO-ROSA et al, 2014). Soy protein concentrate has higher protein and lower carbohydrate contents than ordinary soybean meal but still showed adequate ADC values for Nile tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…De hábito alimentar onívoro tendendo a carnívoro (Rodrigues et al, 2012;Fracalossi & Cyrino, 2013) apresentando o trato digestório gastrointestinal simples, e ausência de cecos pilóricos ou moela (Baldisserotto et al, 2014).…”
Section: Introductionunclassified